Profil biochimique des patients atteints de Covid- 19 hospitalisés à l’EPH de Sidi Ali (Mostaganam) - Midoune, Amel (My University, 2022)
Covid-19 is a global health emergency. The course of the disease is unpredictable with disastrous socio-economic consequences. The objective of our work is to evaluate some biochemical parameters (glycaemia, urea, creatinine, TGO, TGP and CRP) and see their influence on the appearance and development of Covid-19 For this, a retrospective epidemiological survey was carried out in the Sidi Ali hospital in Mostaganem over a period of 2 months (from March 13, 2022 to May 13, 2022). The data was collected from a population affected by SARS-CoV-2 (n-55) recruited to the service of Covid-19 (49%) are female and 51% of patients are male. Our results show that there are indeed alterations in biochemical parameters with a significant increase in blood sugar (p-0.0134), urea (p=0.0076), and creatinine (p=0.0461) with age. Patients aged 60 and over being the susceptible. In conclusion, our results confirm that Covid-19 is associated with disturbances of biochemical parameters, thus suggesting their importance in the early detection of this disease in order to avoid secondary complications.
Keywords: COVID-19; SARS-Cov-2; biochemical parameters